Performance In House Maintenance Peralatan Medis Terhadap Kepuasan Penggunaan Alat Medis Menggunakan Kanos Model dan Quality Function Development (studi kasus RS X Jakarta Pusat) - Sulaiman Metere; Yasinta Dewi Kristianti; Okta Zenita Siti Fatimah (Pusat Penelitian dan Pengabdian Masyarakat (PPPM) STIKES Banyuwangi, 2023)
Sulaiman Metere1, Yasinta Dewi Kristianti2, Okta Zenita Siti Fatimah3 1,2,3Universitas Mohammad Husni Thamrin, Jakarta, Indonesia Email korespondensi: yasintakristianti@gmail.com (+62 817-847-031) Abstract Medical devices is a very vital component in hospitals because it is used to treat and diagnose patients. Electromedical technicians as home care for medical equipment in hospitals need to guarantee the availability and reliability of all medical equipment because it is related to patient safety. Therefore it is necessary to measure the performance (performance) of electromedical technicians in hospitals. The user-based-approach method is used to quantify the satisfaction of medical device users through the Kano model and Quality Function Deployment (QFD) where the coefficients of satisfaction and dissatisfaction are calculated using the Extent of Satisfaction (ES) and Extent of Dissatisfaction (ED) formulas. The results of this study note that from 15 performance attributes there are 9 attributes including the One Dimensional (O) category, namely service quality (ES=1), computerized maintenance management system or CMMS (ES=1), administration (ES=1), dependability (ES=0.89), knowledge sharing (ES=0.89), clarity of SPO (ES=0.89), type of equipment (ES=0.67), attitude (ES=0.67), accuracy of diagnosis (ES=0.56) and 2 attributes included in the Must be category (M), namely flexibility and routine reporting (ES = 0.56) and 4 categories of Attractive attributes (A) namely human resources (ES = 1), technical ability (ES = 1), turn around time ( ES = 0.78), availability of spare parts (ES = 0.67). Performance in house maintenance attributes that need to be improved are the implementation of manual procedures, the number of trainings and competency tests because they have the highest Relative Weight (RW = 11%) and Technical Important Rating (TIR = 573.1; 544.8). Keywords: in house maintenance, Medical Device, Kano Model, QFD